P Pura Bukit Durga Kutri Suatu Analisis Pendidikan Agama Hindu - I Made Suparma Netra I Made Suparma Netra (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to determine, (1) the history of the establishment of the Bukit Durga Kutri Temple in Buruan Village, Blahbatuh, Gianyar (2) The position of the Bukit Durga Kutri Temple in Buruan Village, Blahbatuh, Gianyar, Bali, (3) The function of the Bukit Durga Kutri Temple in terms of from the perspective of Hinduism. This study uses a qualitative approach. The theories used in this study are: 1) Structural Functional Theory, 2) Social Systems Theory, 3) Symbol Theory. Informants were selected using the snowball technique. Data collection was carried out by observation, structured interviews, documentation, and literature study. Data analysis techniques are carried out through a process of reduction, presentation, and drawing conclusions, and the last stage is the presentation of research results. The results of the study show that the history of the establishment of the Bukit Durga Kutri Temple in Buruan Village is closely related to the arrival of King Udayana's consort named Ratu Gunapriyadharpatni from Java. Referring to the educational function of a temple, Bukit Durga Kutri Temple has enormous potential as a learning resource that can be used especially in learning the history of the development of Hinduism in Bali. Pura Bukit Durga Kutri has quite a lot of remains in the form of statues. Seeing from the existence of a Buddha statue in a temple in Bali, we can analyze that the life of people of different religions in the past lived side by side and could respect one another.